Chip Design Hardwires Security. - Adee, S.
Computer security is war. Security experts are in a constant arms race against the ingenuity of hackers. New microprocessor architecture keeps hackers at bay without compromising security.
Keywords: Chip design hardwires security; Computer architecture; Computer security; Microprocessor architecture; Privacy